Gender differences in careers - Antti Kauhanen; Sami Napari (The Research Institute of the Finnish Economy (ETLA), 2011)
We examine gender differences in careers using a large linked employer-employee dataset on Finnish white-collar manufacturing workers over the period of 1981-2006. Our focus is on labour market entrants whom we follow over time. We find that men start their careers from higher ranks of the hierarchy than women do, although gender differences in education explain much of this gap. Men are also more likely to be promoted than women, especially during the first years in the labour market, amplifying the gender differences in hierarchical positions already apparent at labour market entry. Men earn higher starting wages than women, while the results concerning gender differences in the returns to career progression are not clearcut, but depend on the type of career event and on the career phase. Overall, our results helps to understand the factors behind the large increase in the gender wage gap during the early career observed in the earlier literature.
Keywords: J16; J24; J31; J62; 330; careers; internal labour markets; promotions; mobility; wage growth; gender wage gap